Time, history, and political thought - Robertson, John 1951- (Cambridge University Press, 2023)
Between the cliché that 'a week is a long time in politics' and the aspiration of many political philosophers to give their ideas universal, timeless validity lies a gulf which the history of political thought is uniquely qualified to bridge. For that history shows that no conception of politics has dispensed altogether with time, and many have explicitly sought legitimacy in association with forms of history. Ranging from Justinian's law codes to rival Protestant and Catholic visions of political community after the Fall, from Hobbes and Spinoza to the Scottish Enlightenment, and from Kant and Savigny to the legacy of German Historicism and the Algerian Revolution, this volume explores multiple ways in which different conceptions of time and history have been used to understand politics since late antiquity. Bringing together leading contemporary historians of political thought, Time, History, and Political Thought demonstrates just how much both time and history have enriched the political imagination